LANGUAGE AND GENDER FOUND IN “RAYA AND THE LAST DRAGON MOVIE” (SOCIOLINGUISTICS ANALYSIS) - Ravika Yulita; Vera Magria; Dodi Oktariza (Universitas Muara Bungo, 2022)
This research analyzes about Linguistics Feature and kind of Genderlect Style, particularly focusing on language and gender different between men and women in Raya and The Last Dragon Movie. The purpose of this research is to analyze the form of linguistics feature and find out the kind of Genderlect Style used between men and women in language and gender based on Raya and The Last Dragon Movie. In this research, the writer uses a descriptive qualitative method, meanwhile for collecting the data used the non participant observational (SBLC). the data is formed in Pictures and conversation were also used to help the writer draw conclusions. In analyzing the data, the writer use data reduction and data display. The data codes in the form of word, phrase, and sentences spoken by the men and women characters. The result of the study reveals some finding: first, the writer analyzed nine forms of linguistic feature based on Robin Lakoff (1975) but through the analysis, the writer only found six of them out of linguistic form that existed in conversation between men and women are contained in 69 data. There are 33 data of Lexical Hedges and Fillers, 5 data of Tag Questions, 14 data of Super Polite Forms, 4 data of Adjectives, 2 data of Avoidance of strong swear words, 10 data of emphatic stress. The most dominant linguistics features is lexical hedges and fillers with total number 33 data. Second, the writer found five kinds of Genderlect Style based on Tannen (2012) theory. Those are private vs. public, telling story, listening, asking question, and conflict. Finally from five kinds of differences language use between men and women based on Tannen theory, all of the kind can be clearly proven. In this movie, dialogue/codes are dominated by women than man. In addition, the codes between men and women in one scene are limited.